Association Between Length of Stay in the Intensive Care Unit and Sarcopenia Among Hemiplegic Stroke Patients - Aeri Jang; Chang Hoon Bae; Soo Jeong Han; Hasuk Bae (Annals of Rehabilitation Medicine, 2021)
Objective To discuss the association between the length of stay at the intensive care unit (ICU) and sarcopenia among hemiplegic stroke patients. Methods This study evaluated 66 hemiplegic stroke patients with history of ICU admission using handgrip strength and bioelectrical impedance analysis to obtain height-adjusted appendicular skeletal muscle mass. The diagnosis of sarcopenia was made according to the muscle mass based on the Asian Working Group for Sarcopenia. The patients were divided into sarcopenic and non-sarcopenic groups. The two groups were statistically analyzed, and the significant factors with differences were studied. A multivariate logistic regression analysis was performed to examine the association between length of stay in the ICU and sarcopenia, after adjusting for potential confounders. Results Among 66 hemiplegic patients with an ICU admission history, 12 patients were diagnosed with sarcopenia. Sarcopenia patients showed lower scores on the Korean version of the Modified Barthel Index and the Korean version of the Mini-Mental State Examination. Additionally, patients with sarcopenia had a longer length of stay in the ICU, and univariate and multivariate analyses confirmed that the ICU length of stay was significantly related to sarcopenia (adjusted odds ratio=1.187; 95% confidence interval, 1.019–1.382; p=0.028). Conclusion The length of stay in the ICU was significantly associated with sarcopenia in hemiplegic stroke patients.